2013
DOI: 10.3389/fpsyg.2013.00546
|View full text |Cite
|
Sign up to set email alerts
|

Manipulations of word frequency reveal differences in the processing of morphologically complex and simple words in German

Abstract: We tested current models of morphological processing in reading with data from four visual lexical decision experiments using German compounds and monomorphemic words. Triplets of two semantically transparent noun-noun compounds and one monomorphemic noun were used in Experiments 1a and 1b. Stimuli within a triplet were matched for full-form frequency. The frequency of the compounds' constituents was varied. The compounds of a triplet shared one constituent, while the frequency of the unshared constituent was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 54 publications
3
19
0
Order By: Relevance
“…He found response times to be longer when the second constituent was of low than high frequency. Similar results have been obtained by using the lexical decision task (Bronk et al, 2013; Duñabeitia et al, 2007; Inhoff et al, 2008; M. Wang et al, 2010).…”
supporting
confidence: 84%
“…He found response times to be longer when the second constituent was of low than high frequency. Similar results have been obtained by using the lexical decision task (Bronk et al, 2013; Duñabeitia et al, 2007; Inhoff et al, 2008; M. Wang et al, 2010).…”
supporting
confidence: 84%
“…Differently from English, with its open forms such as tree house, German compounds are consistently written as a single string (Baumhaus). Accordingly, many psycholinguistic studies on semantic transparency are being conducted using German compounds (e.g., Böhl, 2007;Bronk et al, 2013;Dohmes, Zwitserlood, & Bölte, 2004;Gumnior, Bölte, & Zwitserlood, 2006;Koester, Gunter, & Wagner, 2007;Lorenz, Heide, & Burchert, 2014;Lorenz & Zwitserlood, 2014;Sahel, Nottbusch, Grimm, & Weingarten, 2008;Smolka & Libben, 2017).…”
Section: The Present Dataset and Related Workmentioning
confidence: 99%
“…Whereas Fiorentino and Poeppel (2007) found evidence for the decomposition of compounds by comparing them to monomorphemic words, other studies have looked for evidence of decomposition by directly comparing compounds whose properties were manipulated. Bronk, Zwitserlood, and Bölte (2013) found that German participants in a lexical decision task recognized compound nouns with highfrequency first constituents (e.g., Papierhut Bpaper hat^) more quickly than compound nouns with low-frequency constituents (e.g., Zauberhut Bmagic hat^), even when controlling for the whole-word frequency of the compounds. Other studies that have manipulated the frequency of the first constituent independently of the second have found effects, in languages including English (Andrews 1986;Juhasz, Starr, Inhoff, & Placke 2003;Shoolman & Andrews, 2003;Taft, 1979;Taft & Forster, 1976) and Chinese (Taft, Huang, & Zhu, 1994).…”
Section: Lexical Decisionmentioning
confidence: 95%
“…There are also suggestions that constituent frequency effects are not equally reliable across languages (see, e.g., Dronjic, 2011, for a discussion of Chinese) and that their appearance may depend on external factors such as task difficulty. For example, Bronk et al (2013) found that manipulating pseudoword foils modulated compound-processing effects (see also Andrews, 1986). It would appear, then, that lexical decision studies do not provide conclusive evidence for full or automatic decomposition.…”
Section: Lexical Decisionmentioning
confidence: 99%